Struktur Kepribadian dan Mekanisme Pertahanan Ego Tokoh Utama dalam Naskah Drama Al-Wajhu Al-Muẓlim li Al-Qamar Karya Najib Kailani - Ahmad Sirfi Fatoni (Study Program of Arabic Language Teaching, 2020)
This article aims to peel the structure of the main character psychological condition and the defense mechanisms of his ego by using Freud's psychoanalysis theory. This is because the drama script has a very complicated problem which is experienced by the main character, Salim, in his life. He had despaired and felt that his life was empty because he got several influences from western culture. The personality structure, according to Sigmund Freud, is divided into three: id, ego and superego. This research is descriptive qualitative research. The result of this research is that personality structure which consists of id, ego and superego was found in Salim's figure. However, the dominating one is the id, then the ego, and the last superego. The researcher can make a hierarchy of personality structure of the main character, Salim, based on his research as (1) the personality structure in the form of id occupies the first level because its appearance is very intense; (2) the personality structure in the form of ego occupies the second level because its appearance is not as much as the id, (3) The personality structure in the form of superego occupies the third level because Salim rarely uses in conscience based on good or bad morality. Meanwhile, the ego defense mechanism found by the researcher in this drama script is (1) repression, (2) displacement or diversion, (3) rationalization, and (4) direct aggression. The others were not found in the drama script. The defense mechanism of the ego displacement becomes one often done by Salim figure to avoid the problem and the psychological conflict that he experienced. The reason is that he diverts feelings of displeasure towards an object to other objects that are more likely to be used as a backrest in the complicated conflict in himself. He considers that the defense mechanism of the ego's displacement felt more secure so as not to add to the complicated problem that he faces.